Wage Subsidy and Labour Market Flexibility in South Africa - Go, Delfin S. (2012)
We use a general equilibrium model to analyse the employment effects and fiscal cost of a wage subsidy in South Africa. We capture the structural characteristics of the labour market with several labour categories and substitution possibilities, linking the economy-wide results to a micro-simulation model with occupational choice probabilities to investigate the poverty and distributional consequences. The employment impact depends greatly on the elasticities of substitution of factors of production, being very minimal if unskilled and skilled labour are complements in production. The impact is improved by supporting policies, but the gains remain modest if the labour market is rigid.